t+8 = 2-3t add 3t to both sides: 4t+8 = 2 take 8 away from both sides: 4t = -6 divide both sides by 4: t = -6/4 = -3/2
(7 + 8)/3 = t Therefore, t = 5.
t=-4
8 t-8 = 4 t = 8+4 t = 12
8
If 4t + 5 = 37, then t = 8.
-3t3 + 23t2 + 8t = -t(3t2 - 23t - 8) = -t(3t + 1)(t - 8)
t+12-8 = t+4
(7 + 8)/3 = t Therefore, t = 5.
t=-4
8 t-8 = 4 t = 8+4 t = 12
-(t(3t + 1)(t - 8))
8
The answer for ( t + (-3) = 8 ) can be found by adding 3 to both sides of the equation to isolate the variable t. This results in ( t = 11 ), as the negative 3 and positive 3 cancel out, leaving t equal to 8 plus 3. Therefore, the solution for the equation is t equals 11.
2t+8-t=-3(t+t)+8-t=-3-8 -8(t+t)-t=-11the -t and the +t cancel outt=-112(-11)+8-(-11)=-3-22+8+11=-3
If 4t + 5 = 37, then t = 8.
t in this problem equals -3. 4t- 8+ 25= 5 -25 -25 4t- 8= -20 +8 +8 4t= -12 /4 /4 t= -3
t would be -5. How I solved this: = 3_t_ + 7 = -8 = 3_t =_ -8 - 7 = 3_t_ = -15 = t = -15/3 = t = -5